2016
DOI: 10.4012/dmj.2016-140
|View full text |Cite
|
Sign up to set email alerts
|

Fracture toughness of seven resin composites evaluated by three methods of mode I fracture toughness (<i>K</i><sub>Ic</sub>)

Abstract: This study compared the fracture toughness values of seven resin composites and analyzed the consistency of data values using three methods: compact tension, three point and four point bending for Mode I failure. Seven resin composites were selected: Estellite Sigma Quick, Esthet X HD, Filtek Supreme XTE, Heliomolar, Ice, Rok, and Vit-l-escence. For each material, 18 specimens (n=6 for each test) were prepared. Maximum load to failure was recorded using a universal testing machine and fracture toughness was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 18 publications
0
4
1
Order By: Relevance
“…X modulus also was similar to that reported by Ilie and Hickel 50) similar to that Blackham et al 55) but greater than reported by Rodrigues et al 53) . Fracture toughness values for Dyract eXtra in this study are less than Yap et al 57) while Esthet X HD fracture toughness results are generally lower than what is reported in other studies [57][58][59][60] , and TPH3 fracture toughness was comparable to that reported of an earlier marketed version by Kim et al 25) but less than that reported by Sookhakiyan et al 61) .…”
Section: Discussioncontrasting
confidence: 68%
“…X modulus also was similar to that reported by Ilie and Hickel 50) similar to that Blackham et al 55) but greater than reported by Rodrigues et al 53) . Fracture toughness values for Dyract eXtra in this study are less than Yap et al 57) while Esthet X HD fracture toughness results are generally lower than what is reported in other studies [57][58][59][60] , and TPH3 fracture toughness was comparable to that reported of an earlier marketed version by Kim et al 25) but less than that reported by Sookhakiyan et al 61) .…”
Section: Discussioncontrasting
confidence: 68%
“…Therefore, KIC is an informative when attempting to predict the longevity of provisional restorations in the intraoral environment. There are several methods of evaluating K IC, and specimen geometry and crack configuration are dependent on the test methods used 20) . In another study, the KIC values of seven resin composites were evaluated using three different methods; the authors concluded that the four-point method provides the greatest discrimination, although the four-and three-point bending tests yielded similar K IC values 20) .…”
Section: Discussionmentioning
confidence: 99%
“…To obtain the K IC values (MPa•m 1/2 ) of four provisional resin-based composites, the single-edge notched-beam (SENB)-type three-point bending test was used 20) . The procedure for making specimens for the KIC test was similar to that used for the σF test except in terms of specimen configuration.…”
Section: Fracture Toughness Measurementsmentioning
confidence: 99%
“…Based on the experimental results, the correlation coefficients were calculated, as well as the characteristic average values of fracture toughness for each individual test. The highest fracture toughness values of dental resins were obtained in four-point bending tests [23].…”
Section: Introductionmentioning
confidence: 94%
“…The stress intensity factors are depicted in Table 2 for both types of adhesives and for all loading directions. The K values denoted as high correspond to the fourth-generation adhesive Allbond3, which has a considered mode I fracture toughness of 1.52 MPa•m 1/2 , while low denotes the SIFs of the universal adhesive Clearfil, with a considered mode I fracture toughness of 0.62 MPa•m 1/2 [22][23][24][25]28].…”
Section: Fea Simulation Of Crack Propagationmentioning
confidence: 99%